2022
DOI: 10.4062/biomolther.2022.044
|View full text |Cite
|
Sign up to set email alerts
|

MHY2251, a New SIRT1 Inhibitor, Induces Apoptosis via JNK/p53 Pathway in HCT116 Human Colorectal Cancer Cells

Abstract: Despite the recent advances in diagnostic and surgical techniques, colorectal cancer (CRC) remains the third most frequently diagnosed cancer and second most common cause of cancer-related mortality worldwide (Li, 2018). CRC is mainly treated by surgical removal, radiotherapy, chemotherapy, or a combination of surgery and chemotherapy (Yang et al., 2017). Despite various treatment strategies, many patients with CRC continue to experience relapse-hence, improved chemotherapeutic agents that can effectively indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…In agreement with earlier ndings (33,42), we documented that SP600125 induced increased rate of apoptosis, coupled with reduced cell viability and increased rate of cells in G2/M phase. While our results were in accord with most studies which concluded that activation of JNK pathway was pro-apoptotic and was counteracted by SP600125 (33,35), they were in apparent disagreement with an earlier study which reported that inhibition of the JNK pathway by SP600125 enhanced TQ-induced apoptosis and increased overall caspase-3 activity in colon cancer DLD-1 cells (22). While not addressed by the authors, this apparent synergy between SP600125 (and thus JNK pathway) and TQ phosphorylation appears to be both cell-type and stimulus speci c.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with earlier ndings (33,42), we documented that SP600125 induced increased rate of apoptosis, coupled with reduced cell viability and increased rate of cells in G2/M phase. While our results were in accord with most studies which concluded that activation of JNK pathway was pro-apoptotic and was counteracted by SP600125 (33,35), they were in apparent disagreement with an earlier study which reported that inhibition of the JNK pathway by SP600125 enhanced TQ-induced apoptosis and increased overall caspase-3 activity in colon cancer DLD-1 cells (22). While not addressed by the authors, this apparent synergy between SP600125 (and thus JNK pathway) and TQ phosphorylation appears to be both cell-type and stimulus speci c.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies reported on the contribution of JNK cascade to apoptosis, highlighted by the ndings that JNK induced cell cycle arrest and apoptosis in osteosarcoma (33), multiple myeloma (34), colorectal cancer (35), and HT-1080 brosarcoma (36) cells. We demonstrated that induction of apoptosis by TQ was linked with inhibition of the phosphorylation and blockade of JNK1/2 pathway, which was con rmed by the anti-apoptotic capacity of the JNK1/2 inhibitor, SP600125.…”
Section: Discussionmentioning
confidence: 99%
“…1A , 1B ). The proliferation of cancer cells could be blocked either by initiating the apoptotic pathway, or inactivating the survival pathway ( Wong, 2011 ), and the induction of apoptosis could be a promising strategy for antineoplastic therapy ( Kang et al ., 2023 ). Therefore, we investigated whether domperidone induced apoptosis in TNBC BT-549 and CAL-51 cells, given that we observed its cytotoxic effects on these cells.…”
Section: Discussionmentioning
confidence: 99%